EDUKASI TANDA DAN GEJALA EPILEPSI PADA SISWA MADRASAH ALIYAH DI LINGKUNGAN PESANTREN AL-ISHLAHUDDINY KEDIRI LOMBOK BARAT SEBAGAI UPAYA PENINGKATAN KESADARAN DALAM HARI KEWASPADAAN EPILEPSI SEDUNIA - Diayanti Tenti Lestari; Ilsa Hunaifi; Safat Wahyudi; Lalu Ahmad Gamal Arigi; Marthin Fernandes Pasaribu; Baiq Holisatul Ismiana; Oktavianus Prayitno (Jurnal Abdi Insani, 2026)
Epilepsy is a chronic neurological disorder that is still frequently associated with stigma due to limited public knowledge regarding its signs, symptoms, and management, which may increase the risk of delayed treatment and complications during seizures. Adolescents, as a productive age group, play an important role in improving health literacy within their communities; therefore, health education efforts are needed to enhance understanding and preparedness regarding epilepsy. This activity aimed to improve students’ knowledge of the signs and symptoms of epilepsy as well as their preparedness in managing seizure events in the school setting. The method used was participatory education, including a pre-test, educational session using PowerPoint media, interactive discussion, and post-test among approximately 100 tenth-grade students at Pondok Pesantren Al Ishlahuddiny, Kediri, West Lombok. The results showed a significant increase in knowledge, with the mean score rising from 4.95 in the pre-test to 6.98 in the post-test, accompanied by an increase in the proportion of participants with high knowledge and a decrease in those with low knowledge. Participants’ enthusiasm was reflected in their active engagement during discussions and question-and-answer sessions. Therefore, school-based health education is effective in improving students’ knowledge and preparedness regarding epilepsy and has the potential to reduce stigma in the community.